Understanding the context for nutrition-sensitive agriculture in Cambodia. NSA Primer - Series 1 - Chuon, Sophea; Monville, Emilita Oro; Umali, Diana Jean A.; Or, Thy; Pham Thi, Huong Mai; Duong, Thanh Thi; Huynh Thi, Tuyen Thanh; Nabuuma, Deborah; Gonsalves, Julian (2024)
Cambodia has made significant strides in socioeconomic development, aiming to become an upper middle-income country by 2030 and a high-income country by 2050. However, rural agriculture and livelihoods face challenges amid a changing food system and economic landscape. To strengthen ongoing efforts, a nutrition- and gender-sensitive approach is crucial. This primer series explores Cambodia's context and key concepts for nutrition-sensitive agriculture, emphasizing the need for sustainable solutions to ensure food and nutrition security while supporting rural communities.